Oxidative and Nitrosative-based Signaling and Associated Post-translational Modifications Orchestrate the Acclimation of Citrus Plants to Salinity Stress - Fotopoulos, Vasileios; Filippou, Panagiota S.; Tanou, Georgia (My University, 2012)
Reactive oxygen and nitrogen species are involved in a plethora of cellular responses in plants; however, our knowledge on the outcomes of oxidative and nitrosative signaling is still unclear. To better understand how oxidative and nitrosative signals are integrated to regulate cellular adjustments to external conditions, local and systemic responses were investigated in the roots and leaves of sour orange plants (Citrus aurantium L.) after root treatment with hydrogen peroxide (H 2O 2) or sodium nitroprusside (a nitric oxide donor), followed by NaCl stress for 8 days. Phenotypic and physiological data showed that pre-exposure to these treatments induced an acclimation to subsequent salinity stress that was accompanied by both local and systemic H 2O 2 and nitric oxide (NO) accumulation. Combined histochemical and fluorescent probe approaches showed the existence of a vascular-driven long-distance reactive oxygen species and NO signaling pathway. Transcriptional analysis of genes diagnostic for H 2O 2 and NO signaling just after treatments or after 8 days of salt stress revealed tissue- and time-specific mechanisms controlling internal H 2O 2 and NO homeostasis. Furthermore, evidence is presented showing that protein carbonylation, nitration and S-nitrosylation are involved in acclimation to salinity stress. In addition, this work enabled characterization of potential carbonylated, nitrated and nitrosylated proteins with distinct or overlapping signatures. This work provides a framework to better understand the oxidative and nitrosative priming network in citrus plants subjected to salinity conditions
Keywords: Citrus; Nitration; Proteomics; Hardwoods; Hydrogen peroxide; Molecular biology; Nitric oxide; Oxygen; Physiology; Plants; Proteins; Sodium